Synthesis, Characterization and Antifungal Activity of Mn(II), Co(II), Ni(II) and Cu(II) Complexes with 4-Hydroxybenzaldehyde-N-4'-cytidinylazomethine - Singh, Pratibha; Kumar, Vikas; Kumar, Manoj (Asian Journal of Chemistry, 2010)
Synthesis of Mn(II), Co(II), Ni(II) and Cu(II) complexes of 4-hydroxybenzaldehyde-N-4'- cytidinylazomethine has been described and their structures have been established on the basis of elemental analysis, infrared spectra, 1H NMR spectra and magnetic analysis. The complexes have been screened for their antifungal potential against some fungal strains viz., Aspergillus niger and Aspergillus flavus. The minimum inhibitory concentrations of the Schiff bases and metal complexes were determined by filter paper disc method. The result reveals that the antifungal activities of metal complexes are higher than that of the free ligand.